Writing user stories : product management core skills : the user story format (O'Reilly, 2017)
"A user story is always written from the perspective of the product's end user. Note that the business can be the end user in some cases (such as when the feature involves an internal CMS or analytics suite). User stories are written in the format: 'As a user, I want to be able to do [x] so that I can accomplish [y].' If the user story involves a frontend (user-facing) design component, the design files should be included with the user story. In this segment, you'll learn the essential structure of a user story."--Resource description page